AN INVESTIGATION INTO EFL STUDENTS' PERCEPTIONS OF UTILIZING AI FOR PARAPHRASING IN ACADEMIC ENGLISH WRITING CLASS - Asriani Hasibuan; Derlina Sari Rambe (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this research is to find out how the EFL Students' perceptions of using AI Paraphrasing Tool and the factors influencing the EFL Students' perceptions of using AI Paraphrasing Tool in Academic English Writing Class at the Eighth Semester of English Language Education Study Program South Tapanuli Education Institute . The informants of this research consist of 15 students. The researcher uses purposive sampling technique to get the subjects or informants. The data was obtained by distributing the questionnaire and interviewing for the informants. It is found that the result of the EFL Student's perceptions of using AI Paraphrasing Tool in Academic English Writing Class at the Eighth semester of the English Language Education Study Program of the South Tapanuli Education Institute is positive category. The researcher found that the mean score of Strongly Disagree categories (10.3%), Disagree (18%), Neutral (29%) and Agree (20.3%), Strongly Agree (22.3%). Furthermore, the result of factors influencing the EFL Students' perceptions of using AI Paraphrasing Tool in Academic English Writing Class in Academic English Writing Class at the Eighth semester of English Language Education Study Program South Tapanuli Education Institute is external factors more dominant than internal factors. A part of seven factors (Smith (1945), in this study, during the interview process, researchers found that there were other factors that influenced students in making decisions about using AI Paraphrasing Tool, it is a factor of cost.